Bulbs in containers - Rod Leeds (Timber Press, 2005)
Fantastic color photographs and excellent writing make this an inspirational and accessible guide for specialty plant collectors, alpine and rock gardeners, and city gardeners, as well as anyone gardening in small spaces. Readers will learn about the ease and practicality of growing bulbs in containers — bringing year-round color and interest to one's home. Popular classic bulbs are included, as well as a range of more unusual varieties such as the delicate-looking but surprisingly unfussy corydalis, and graceful, late-spring-flowering scillas.